Deletion of a single glycosyltransferase in Caldicellulosiruptor bescii eliminates protein glycosylation and growth on crystalline cellulose - Russell, Jordan (Biotechnol Biofuels, 2018)
Protein glycosylation pathways have been identified in a variety of bacteria and are best understood in pathogens and commensals in which the glycosylation targets are cell surface proteins, such as S layers, pili, and flagella. In contrast, very little is known about the glycosylation of bacterial enzymes, especially those secreted by cellulolytic bacteria. Caldicellulosiruptor bescii secretes several unique synergistic multifunctional biomass-degrading enzymes, notably cellulase A which is largely responsible for this organism’s ability to grow on lignocellulosic biomass without the conventional pretreatment. It was recently discovered that extracellular CelA is heavily glycosylated. In this work, we identified an O-glycosyltransferase in the C. bescii chromosome and targeted it for deletion. The resulting mutant was unable to grow on crystalline cellulose and showed no detectable protein glycosylation. Multifunctional biomass-degrading enzymes in this strain were rapidly degraded. With the genetic tools available in C. bescii, this system represents a unique opportunity to study the role of bacterial enzyme glycosylation as well an investigation of the pathway for protein glycosylation in a non-pathogen. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13068-018-1266-x) contains supplementary material, which is available to authorized users.